2021
DOI: 10.3389/fpsyg.2021.618956
|View full text |Cite
|
Sign up to set email alerts
|

I Am vs. We Are: How Biospheric Values and Environmental Identity of Individuals and Groups Can Influence Pro-environmental Behaviour

Abstract: Most research in environmental psychology is conducted in individualistic countries and focuses on factors pertaining to individuals. It is yet unclear whether these findings also apply to more collectivistic countries, in which group factors might play a prominent role. In the current paper, we test the individual-focused value–identity–behaviour pathway, in which personal biospheric values relate to pro-environmental actions via environmental self-identity, in an individualistic and a collectivistic country.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
59
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 56 publications
6
59
1
Order By: Relevance
“…The third important finding is related to the insignificant relationship between collectivism and inconvenience. These results are not consistent with the findings of many studies, e.g., [44,[46][47][48]. The context of this study is also important and needs reflection at this stage.…”
Section: Discussioncontrasting
confidence: 97%
See 3 more Smart Citations
“…The third important finding is related to the insignificant relationship between collectivism and inconvenience. These results are not consistent with the findings of many studies, e.g., [44,[46][47][48]. The context of this study is also important and needs reflection at this stage.…”
Section: Discussioncontrasting
confidence: 97%
“…Kirmani and Khan [48] found collectivism as a predictor of environmental concern in Indian consumers. Similarly, Wang et al [44] found collectivism as a predictor of green purchase attitude and green purchase intentions in Chinese hotel consumers.…”
Section: Collectivism and Behavioral Intentionsmentioning
confidence: 88%
See 2 more Smart Citations
“…The researchers show that maximizing individual needs under certain circumstances can lead to environmentally responsible behavior, but they cannot "provide a more stable basis for proenvironmental behavior". In several publications, authors consider personal values through the groups of egoistic, hedonic, altruistic, and biospheric values (WANG et al, 2021). At the same time, most studies on environmental behavior do not show differences "between biospheric and altruistic value orientations" (BARDI, SCHWARTZ, 2003;CORRALIZA, BERENGUER, 2000).…”
Section: Literature Reviewmentioning
confidence: 99%